Rawat Gabung Sebagai Penguat Breastfeeding Self-Efficacy pada Ibu Postpartum - Dwi Irawati Agustina; Happy Dwi Aprilina (FORIKES, 2024)
Breastfeeding self-efficacy is a mother's belief regarding her ability to provide breast milk (ASI), which has an important role because it can influence the success of exclusive breastfeeding. This research aimed to compare breastfeeding self-efficacy between postpartum mothers and babies in joint care and in the hospital perinatology treatment room. This research design was cross-sectional, involving 70 postpartum mothers in the combined ward and perinatology ward at the Margono Soekarjo Regional General Hospital, Purwokerto, each ward consisting of 35 respondents. Respondents were selected using a simple random sampling technique. Breastfeeding self-efficacy was measured by completing the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF), which had been tested for validity and reliability. Next, a comparative analysis of breastfeeding self-efficacy was carried out based on the place of care for the baby, using an independent samples t-test. The results of the analysis showed that the p value was 0.029, so it was interpreted that there was a difference in Breastfeeding self-efficacy. It could be concluded that there was a significant difference in breastfeeding self-efficacy between postpartum mothers and babies in the combined care room and in the perinatology care room. Furthermore, it was concluded that joint care strengthens breastfeeding self-efficacy for postpartum mothers.Keywords: breastfeeding self-efficacy; combined treatment room; perinatology treatment room ABSTRAK Breastfeeding self-efficacy ialah kepercayaan ibu mengenai kemampuan dalam pemberian air susu ibu (ASI), yang mempunyai peran penting karena mampu mempengaruhi kesuksesan pemberian ASI eksklusif. Riset ini bertujuan untuk membandingkan breastfeeding self-efficacy antara ibu postpartum dengan bayi di rawat gabung dan di ruang perawatan perinatologi rumah sakit. Desain riset ini adalah cross-sectional, dengan melibatkan 70 ibu postpartum di ruang rawat gabung dan ruang perawatan perinatologi Rumah Sakit Umum Daerah Margono Soekarjo, Purwokerto, masing-masing ruang terdiri atas 35 responden. Responden dipilih dengan teknik simple random sampling. Breastfeeding self-efficacy diukur melalui pengisian Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) yang telah teruji validitas dan reabilitasnya. Selanjutnya dilakukan analisis perbandingan breastfeeding self-efficacy berdasarkan tempat perawatan bayi, menggunakan independent samples t-test. Hasil analisis menunjukkan bahwa nilai p adalah 0,029, sehingga diinterpretasikan bahwa ada perbedaan Breastfeeding self-efficacy disimpulkan bahwa terdapat berbedaan breastfeeding self-efficacy secara signifikan antara ibu postpartum dengan bayi di ruang rawat gabung dan di ruang perawatan perinatologi. Selanjutnya disimpulkan bahwa rawat gabung merupakan penguat breastfeeding self-efficacy bagi ibu postpartum.Kata kunci: breastfeeding self-efficacy; ruang rawat gabung; ruang perawatan perinatologi